Production of Silver Nanoparticles with Strong and Stable Antimicrobial Activity against Highly Pathogenic and Multidrug Resistant Bacteria - Amr T. M. Saeb; Ahmad S. Alshammari; Hessa Al-Brahim; Khalid A. Al-Rubeaan (The Scientific World Journal)
Aims. To synthesize, characterize, and analyze antimicrobial activity of AgNPs of Escherichia hermannii (SHE), Citrobacter sedlakii (S11P), and Pseudomonas putida (S5). Methods. The synthesized AgNPs were examined using ultraviolet-visible spectroscopy (UV-vis) and, zeta potential, and the size and the morphology obtained from the three different isolates were also confirmed by TEM. Results. Among the three isolates tested, SHE showed the best antimicrobial activity due to the presence of small (4–12 nm) and stable (−22 mV) AgNPs. Stability of AgNPs was also investigated and found to be dependent on the nature of isolates. Conclusion. Produced AgNPs showed particle stability and antimicrobial efficacy up to 90 days of production. Our AgNPs exhibited greater antimicrobial activity compared with gentamicin against P. aeruginosa isolates and vancomycin against S. aureus and MRSA isolates at very low concentration (0.0002 mg per Microliters).